OPTIMALISASI SISTEM PENGISIAN AIR OTOMATIS MENGGUNAKAN SENSOR ULTRASONIK BERBASIS MIKROKONTROLER - Lebang, Annamaintin (Charm Sains: Jurnal Pendidikan Fisika, 2025)
Efficient water management is becoming increasingly important due to the increasing demand for water. One of the growing solutions is the implementation of an automatic water filling system that utilizes ultrasonic sensor technology and microcontrollers. The process begins with sensor design and testing, as well as calibration of the HC-SR04 ultrasonic sensor to improve the accuracy of water level measurement. The sensor works by measuring the distance between the sensor and the water surface and then sending the data to the Arduino Uno microcontroller. The microcontroller controls the work of the water pump based on the predetermined upper limit of water. The results show that the system can control water filling automatically. To improve performance, optimization is done by using a water pump, relay, buzzer and several LEDs that will work automatically depending on the water level conditions. Buzzer and three LEDs with different colors act as water level indicators. This automatic water filling system can work optimally with high accuracy and good efficiency in controlling the water level. This research can be further developed with several software simulations for various measurements and on a larger scale.